Peran Komunikasi Interpersonal dalam Meningkatkan Efektifitas Tim di Lingkungan Kerja di Kantor Pos Maumere - Imelda Virgula Wisang; Asdianti Asdianti; Nelci Elvida Klega; Afdal Sayhudin; Yusliani Julein Wole (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This report aims to help improve the quality of interpersonal communication in the Maumere Post Office work environment. Interpersonal communication is a crucial factor in supporting work effectiveness, creating harmonious working relationships, and improving employee performance. The method used in this report is a qualitative approach, with data collection techniques through observation, interviews, and documentation of employees at the Maumere Post Office. This approach was chosen to gain a deep understanding of communication patterns, interactions between employees, and obstacles encountered in the daily communication process. The results of the report indicate that effective interpersonal communication in the Maumere Post Office work environment plays a significant role in improving teamwork, reducing misunderstandings, and creating a conducive work atmosphere. The factors of openness, empathy, mutual respect, and clarity of message delivery are key elements in effective communication. However, several obstacles were still found, such as differences in individual characters and limited communication time. Therefore, this report recommends efforts to improve interpersonal communication through training, habituating open communication, and strengthening working relationships between employees to support the achievement of organizational goals.